Live Streaming, Playing, and Money Spending Behaviors in eSports. Issue 1 (January 2020) - Wohn, Donghee Yvette; Freeman, Guo
Live streaming has enabled eSports to become more accessible, ranging from professionally organized tournaments to individuals hosting from their bedroom. While different aspects of eSports have been investigated in separate contexts, in this article, we report findings of two survey studies to explore eSports as a holistic media ecosystem that includes playing, streaming, viewing, and spending. Study 1 looks at cross-platform patterns between playing and spending within the game as well as between viewing, streaming, and spending on live streaming platforms in the context of Fortnite. Study 2 examines the relationships between viewing and spending patterns on live streaming platforms. Results indicate that playing, viewing, and in-game spending are strongly related. Yet none of these behavioral metrics explain why people spend money on live streaming platforms to support streamers. Rather, psychological factors such as emotional attachment to the streamer and appreciation of the streamers' talents are what drive streamer support.